P2O5/SiO2-Catalyzed solvent-free room-temperature synthesis of 2-aryl-benzimidazoles and their toxicity against Artemia salina - Pansacala, Janus B; Nillama, Joshua Andrew P; Creencia, Evelyn C (Asia-Pacific Journal of Science and Technology, 2025)
Twelve (12) 2-Aryl-1H-benzimidazole derivatives were synthesized from a series of 4-o-phenylenediamines [R: -NO2, -COOCH2CH3, and -COAr] and 4-aryl aldehydes [R: -H, -N(CH2CH3)2, -CH(CH3)2, -CH(OCH2CH3)2] utilizing a simple, cheap, and heterogeneous P2O5/SiO2 catalytic system at room temperature and solvent-free conditions. Moreover, the bioactivity of the prepared benzimidazoles, evaluated via brine shrimp lethality assay (BSLA), showed that almost all benzimidazole products were cytotoxic, except for 5-nitro-2-phenyl-1H-benzo[d]imidazole (5a). Highest activity was observed for 2-(4-isoproylphenyl)-5-nitro-1H-benzo[d]imidazole (5b) with acute lethal concentration (LC50) of 43.42 ppm, whereas the least active N, N-diethyl-4-(5-nitro-1H-benzo[d]imidazol-2-yl) aniline (5c), had chronic LC50 value of 283.39 ppm. Qualitative structure - BSLA activity correlation showed that balanced electron-donating capacity of R2 coupled with electron-withdrawing effect of R1 led to enhanced toxicity of 2-Aryl-1H-benzimidazoles.